Two non-syndromic cases of multiple supernumerary teeth with different characteristics and a review of the literature. Issue 3 (May 2016) - Takahashi, Katsu; Togo, Yumiko; Saito, Kazuyuki; Kiso, Honoka; Huang, Boyen; Tsukamoto, Hiroko; Fujimura, Kazuma; Bessho, Kazuhisa
Abstract: Multiple supernumerary teeth are rare in patients without any associated conditions, and the mechanisms responsible for the development of multiple supernumerary teeth in such patients remain unclear. We report two cases in which multiple supernumerary teeth developed in patients without any associated conditions. The two cases differed with respect to the morphology of the supernumerary teeth, the locations of impacted teeth, and the degree of calcification and development of the supernumerary teeth. Case 1 involved a 13-year-old boy with six impacted supernumerary teeth who was not suffering from any associated conditions. The supernumerary teeth were impacted on the lingual or palatal side of the premolars and canine root apex, were similar in size, and exhibited similar degrees of calcification and development. Case 2 involved a 10-year-old boy without any relevant medical history who had five impacted supernumerary teeth. His supernumerary teeth were distributed in an irregular manner and varied in size, morphology, and the extent of their calcification and development. Genetically modified mouse models have provided some information about the molecular mechanisms underlying the development of supernumerary teeth. We reviewed previous cases of non-syndromic multiple supernumerary teeth based on our findings. We consider that supernumerary teeth can arise via various developmental mechanisms and that similar developmental mechanisms to those seen in mouse models might exist in humans.